Análise da parceria estratégica Portugal Telecom e Companhia Telefónica OI - Gomes, Sara (2012)
One of the basic business principles is to generate value for the company and also for its shareholders and partners. In order to do so there are a few number of strategies that enhance the referred value, such as mergers and acquisitions. When associated to activity sectors that have reached maturity this principle becomes a way of obtaining synergies designed to improve a company’s efficiency and, consequently, incrementing the shareholders/partners profits. The prior problematic is addressed in this paper through a real case study connected with the telecommunications sector. In this study with the metric Economic Value Added the purchase of the OI company by the Portuguese PT (Portugal Telecom) is evaluated, in the years of 2010 and 2011, the synergies that have derived from this acquisition are also analysed.